2012
DOI: 10.1109/tvt.2012.2205596
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Distributed Asynchronous Multichannel MAC Scheme for Large-Scale Vehicular Ad Hoc Networks

Abstract: This paper proposes an analytical model for the throughput of the Enhanced Distributed Channel Access (EDCA) mechanism in IEEE 802.11p MAC sub-layer. Features in EDCA such as different Contention Windows (CW) and Arbitration Interframe Space (AIFS) for each Access Category (AC), and internal collisions are taken into account. The analytical model is suitable for both basic access and the Request-To-Send/Clear-To-Send (RTS/CTS) access mode. The proposed analytical model is validated against simulation results t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
38
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 60 publications
(38 citation statements)
references
References 25 publications
0
38
0
Order By: Relevance
“…The IEEE 1609.4 extension adopts a synchronous switching between control channel and service channels. It is shown that synchronous operation of the MAC sub-layer is an inherently poor utilisation of the DRAFT July 29, 2018 SUBMITTED PAPER 3 bandwidth ( [11], [23], [24]). To mitigate the poor bandwidth utilisation problem of synchronous multi-channel MACs, asynchronous multi-channel MACs were proposed (surveyed in [17]).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…The IEEE 1609.4 extension adopts a synchronous switching between control channel and service channels. It is shown that synchronous operation of the MAC sub-layer is an inherently poor utilisation of the DRAFT July 29, 2018 SUBMITTED PAPER 3 bandwidth ( [11], [23], [24]). To mitigate the poor bandwidth utilisation problem of synchronous multi-channel MACs, asynchronous multi-channel MACs were proposed (surveyed in [17]).…”
Section: Introductionmentioning
confidence: 99%
“…This was further enhanced by introducing hopping sequence to schedule multiple parallel rendezvous [18], applying Pulse/Tone exchanges prior to handshake for collision avoidance on the control channel [19]. In our previous work [11], we proposed a novel distributed asynchronous multichannel MAC scheme in favour of high network load and multiple simultaneous transmissions via Distributed-TDMA mechanism and enhanced channel utilisation. It outperforms well-known existing asynchronous multi-channel MAC schemes such as [7], [8] and [21].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations